Testing of the composition of e-cigarette liquids - Manufacturer-declared vs. true contents in a selected series of products - Małgorzata Kucharska; Wiktor Wesołowski; Sławomir Czerczak; Renata Soćko (Nofer Institute of Occupational Medicine, 2016)
Background: Electronic cigarettes are currently in common use. However, in Poland there is no specific legislation governing the sale of these products. At the same time, no information has been made public about the hazards e-cigarettes pose to the users and bystanders − passive smokers. The aim of the study was to determine the qualitative composition of the analyzed liquid, which is an essential element of regulating the distribution of such cigarettes. Material and Methods: Under this study the method for determining the composition of e-cigarette liquids was developed. This method employs gas chromatography with mass spectrometry (GC-MS). Levels of nicotine and flavoring components were determined in 50 e-liquid samples. The results were compared with the information provided by the manufacturer on the packaging. Results: The applied method of qualitative determination helped to identify the main ingredients, such as nicotine and propylene glycol (PG). Propylene glycol was found to be present in all liquids, because it was used as the solvent for nicotine and flavors. There was a good agreement between the declared and the determined content of nicotine in the analyzed samples. The agreement was considerably poorer for the remaining e-liquid ingredients, mainly flavors. Conclusions: There was no agreement between the flavor substances specified by the manufacturer and aroma identified in the e-cigarette liquid, which may pose a risk to users of e-cigarettes, particularly those susceptible to allergies. Several unsaturated aliphatic alcohols and aldehydes found to be present in the liquids, unstable at elevated temperatures, may be more harmful to the smoker than the original compounds. Therefore, it is essential to implement in Poland the legal provisions regarding e-cigarettes. Med Pr 2016;67(2):239-253